Effect of osmotic dehydration process using sucrose solution at mild temperature on mass transfer and quality attributes of red pitaya (Hylocereus polyrhizusis) - Najafi, Asal Haj; Yusof, Yus Aniza; Abdul Rahman, Russly; Ganjloo, Ali; Chin, Nyuk Ling (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
In the current research, osmotic dehydration of red pitaya (Hylocereus polyrhizusis) cubes using sucrose solution at mild temperature (35ºC) was investigated. Sucrose solution (40, 50 and 60% w/w) was employed for osmotic dehydration process. Responses of weight reduction (WR), solid gain (SG), water loss (WL), color (L* , a* and b* ) and texture (hardness) were evaluated. It was found that sucrose concentration significantly (p < 0.05) affected the mass transfer terms during osmosis process. The results obtained revealed an increase in yellowness (b* ), decrease in lightness (L* ) and redness (a* ) as the sucrose concentration increased. Furthermore, osmotically dehydrated samples were considerably softer than untreated samples. Increasing of sucrose concentration and dehydration time caused softer tissue of dehydrated product compared with the fresh red pitaya.